(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
Collaborative skills are essential 21st-century competencies that university students, particularly in science-based disciplines such as chemistry, must acquire. This article aims to examine strategies for enhancing students’ collaborative skills through the implementation of the Project-Based Learning (PJBL) model. This study employed a theoretical literature review method by analyzing 10 scholarly articles published in reputable national and international journals between 2014 and 2024. Data sources were collected systematically from academic databases such as Google Scholar, Scopus, DOAJ, and ScienceDirect. Thematic analysis was used to identify patterns related to PJBL approaches, indicators of collaborative skills, and challenges in implementation. The review findings indicate that PJBL consistently enhances collaboration through project designs that emphasize teamwork, problem-solving, communication, and collective reflection. Collaboration fostered through PJBL goes beyond task completion and cultivates essential social and academic competencies for workplace readiness. These findings reinforce PJBL as an effective and adaptable pedagogical approach, offering both theoretical and practical insights for educators and curriculum developers in designing contextualized 21st-century learning experiences.